Scaling up antiretroviral therapy in Uganda: using supply chain management to appraise health systems strengthening - Neuhann Florian; Waiswa Peter; Windisch Ricarda; Scheibe Florian; de Savigny Don (BMC, 2011)
Abstract Background Strengthened national health systems are necessary for effective and sustained expansion of antiretroviral therapy (ART). ART and its supply chain management in Uganda are largely based on parallel and externally supported efforts. The question arises whether systems are being strengthened to sustain access to ART. This study applies systems thinking to assess supply chain management, the role of external support and whether investments create the needed synergies to strengthen health systems. Methods This study uses the WHO health systems framework and examines the issues of governance, financing, information, human resources and service delivery in relation to supply chain management of medicines and the technologies. It looks at links and causal chains between supply chain management for ART and the national supply system for essential drugs. It combines data from the literature and key informant interviews with observations at health service delivery level in a study district. Results Current drug supply chain management in Uganda is characterized by parallel processes and information systems that result in poor quality and inefficiencies. Less than expected health system performance, stock outs and other shortages affect ART and primary care in general. Poor performance of supply chain management is amplified by weak conditions at all levels of the health system, including the areas of financing, governance, human resources and information. Governance issues include the lack to follow up initial policy intentions and a focus on narrow, short-term approaches. Conclusion The opportunity and need to use ART investments for an essential supply chain management and strengthened health system has not been exploited. By applying a systems perspective this work indicates the seriousness of missing system prerequisites. The findings suggest that root causes and capacities across the system have to be addressed synergistically to enable systems that can match and accommodate investments in disease-specific interventions. The multiplicity and complexity of existing challenges require a long-term and systems perspective essentially in contrast to the current short term and program-specific nature of external assistance.